PROSES PERUMUSANKEBIJAKAN UPAH MINIMUM KOTA SEMARANG 2016 - Vivie Kartika Ayu; Zainal Hidayat (Journal of Public Policy and Management Review, 2017)
Labor is waging a problem that continues to happen every year, including in the city of Semarang, where frequent disagreements between workers and employers in formulatating wage mainly in 2016. The city's minimum wage is a standard party entrepreneurs provide retribution to workers or labor against his work. The process of formulation of the minimum wage of waging the Council conducted a survey rating the necessities of life are worthy (KHL) during the months of January to September, while October to December as value predictions. The survey is conducted in some traditional markets in the city of Semarang. The results of the surveys discussed inwaging Town Council meeting comprising the Government, employers and trade unions. Then after the results of the meeting of the city's wages granted by the Mayor to further the results submitted to the Governor of Central Java. Model Formulationused in this study is a model of the process while a cornerstone of the theory is the theory used of stages of policy formulation by Budi Winarno theory consists of the formulation of the plobem , the policy agenda, the selection of an alternative policy,as well as the setting of the policy. The research method is qualitative diskriptifmethod. While data collection technique of using observation, interviews, and documentation. Results of the study says the minimum wage policy formulation process Semarang city conducted by wiging councils went well which follows from the regulatations. As for the actors involved in the process of formulation of the Semarang city minimum wage policy consists of three elements i.e. the Government, employersand labor unions are joining in a non sctuctural named waging waging Semarang City Council.